Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd006911.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Music interventions for improving psychological and physical outcomes in cancer patients

Abstract: This systematic review indicates that music interventions may have beneficial effects on anxiety, pain, mood, and QoL in people with cancer. Furthermore, music may have a small effect on heart rate, respiratory rate, and blood pressure. Most trials were at high risk of bias and, therefore, these results need to be interpreted with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
247
5
25

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 246 publications
(290 citation statements)
references
References 40 publications
13
247
5
25
Order By: Relevance
“…Music is a widely used leisure activity which has demonstrated a capacity to improve well-being (Bradt et al, 2011;MacDonald et al, 2012;Rickard and McFerran, 2012) and impact on symptoms of mental illness, such as depression and anxiety (Bradt and Dileo, 2009;Maratos et al, 2008;Siedliecki and Good, 2006). Music can be used to cope with life stressors and is not only cited as a personal mood management strategy (DeNora, 2000;Hays and Minichiello, 2005;Laukka, 2007;Saarikallio, 2007;Sloboda, 1999), but is also used frequently in hospital settings to reduce pain, anxiety or stress, and even to reduce the length of hospitalization (Standley, 1995).…”
Section: The Role Of Music In Promoting Mental Healthmentioning
confidence: 99%
“…Music is a widely used leisure activity which has demonstrated a capacity to improve well-being (Bradt et al, 2011;MacDonald et al, 2012;Rickard and McFerran, 2012) and impact on symptoms of mental illness, such as depression and anxiety (Bradt and Dileo, 2009;Maratos et al, 2008;Siedliecki and Good, 2006). Music can be used to cope with life stressors and is not only cited as a personal mood management strategy (DeNora, 2000;Hays and Minichiello, 2005;Laukka, 2007;Saarikallio, 2007;Sloboda, 1999), but is also used frequently in hospital settings to reduce pain, anxiety or stress, and even to reduce the length of hospitalization (Standley, 1995).…”
Section: The Role Of Music In Promoting Mental Healthmentioning
confidence: 99%
“…This is a common problem across this field. 9 More generally, studies such as ours face a constant challenge obtaining negative evaluations:…”
Section: Discussionmentioning
confidence: 99%
“…Overall, mental health team members who had experience of referring service users to art therapy overwhelmingly reported that art therapy was an important treatment in mental 9 9 health services. Key benefits identified included reducing social isolation, building confidence, providing a positive activity with opportunity for self-expression.…”
Section: Staff Survey and Qualitative Feedbackmentioning
confidence: 99%
“…Thirty randomized clinical trials on cancer patients to study the effect of music therapy include listening to recorded music on cancer patients have shown anxiety reduction by cortisol suppression, mood improvement and blood pressure reduction. It is also acts on mental health and immune function in patients with cancer by emotional expression, social support and benefit finding [30,31,34,35,42].…”
Section: Clinical Studies Of Beta Endorphins On Different Types Of Camentioning
confidence: 99%